Karakteristik Tepung Kulit Pisang Modifikasi Menggunakan Hydrogen Rich Water - budiarti, Gita Indah; Sulistiawati, Endah; Septiani, Nona; Septianindi, Windi (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2021)
Banana peels are rich in fiber and antioxidants that are good for health. Banana peels can be used as flour. However, banana peel flour does not expand as well as flour. Starch modification is needed to improve the physicochemical properties of banana peel flour. Starch modification using Hydrogen Rich Water (HRW) is safer and cheaper than other methods. The novelty of this study is that there are no studies using HRW to modify banana peel flour. The purpose of this study was to determine the physical characteristics, reducing sugar content and protein content of HRW modified banana peel flour according to the standard SNI flour 3751: 2009. The main ingredients used are banana peels and HRW. Experiments were carried out by immersing banana peels in HRW for 15.30,45,60,75 minutes and pH (5 and 9). The results obtained were no changes in the physical characteristics of modified banana peel flour. The best results of sugar and protein content were obtained at pH 5. The best reducing sugar content at 60 minutes immersion was 2.1575%. The best protein content was obtained at 15 minutes immersion of 4.2152%.